Strategic thinking as an intermediate variable in enhancing the impact of strategic vigilance On strategic success - شيروان عمر اومر (QALAAI ZANIST SCIENTIFIC JOURNAL, 2019)
The aim of the research is to identify the role of strategic thinking as a mediator between strategic alertness and strategic success, namely the following dimensions (strategic intent, time thinking, guided hypotheses, opportunistic thinking, systemic thinking), and the effect of strategic vigilance as an independent variable with its four dimensions: , Marketing vigilance, environmental vigilance) in strategic success and survival (adaptation, growth) as a dependent variable and applied to private banks in the city of Erbil. The research problem was shaped by a number of intellectual and practical questions. It consisted of delving into the levels of strategic alertness and its impact on the levels of strategic success through the medium variable strategic thinking. To achieve the goal, the questionnaire was designed as the main data collection tool, which included (60) statements distributed to a sample of the managers of the private sector banks. The total number of directors (122) from the research community represented by all the managers of private sector banks in Erbil, ) As a director, and the descriptive analytical approach was adopted as a research method. For the purposes of statistical analysis, the statistical program SPSS was used to empty and analyze the questionnaire using a set of statistical methods such as arithmetic mean, standard deviations, and simple and multiple regression. The research found a relationship of correlation and influence between strategic thinking and strategic vigilance in strategic success. Based on the research findings, a number of proposals were presented.